Bibliometric Mapping of Factors Influencing Compliance in Nursing Care Documentation - Sai'ah Sai'ah; Syamsul Arifin; Mohamad Isa; Meitria Syahdatina Noor; Lenie Marlinae (Malahayati Nursing Journal, 2024)
ABSTRACT Accurate and complete nursing documentation plays an important role in ensuring the quality of nursing care and patient safety. However, adherence to documentation standards among nurses often remains a challenge that affects the overall quality of medical records and clinical interventions. This study was conducted to map research trends and factors affecting compliance in nursing documentation through a bibliometric analysis approach. The main objective of this study was to identify the main topics, key factors, as well as emerging publication trends related to nursing documentation compliance over the past few years. This study used the Publish or Perish application to collect 50 scientific articles published between 2016 and 2024, with keywords such as "compliance", "completeness", and "nursing care documentation". The data obtained was then analyzed using VOSviewer to visualize the bibliometric network based on the keywords that appeared in the literature. Through Network Visualization, Overlay Visualization, and Density Visualization, this study identified the main keywords such as "completeness", "motivation", "knowledge", and "compliance" that were most frequently discussed in related studies. The results of the analysis showed that documentation completeness and its influencing factors, such as nurse motivation and knowledge, are the main focus in the documentation compliance literature. In addition, the publication trend shows a significant increase in 2020 and 2021, most likely related to the COVID-19 pandemic situation that drives increased attention to the quality of documentation in healthcare. The conclusion of this study shows that adherence in nursing documentation, specifically related to the completeness, motivation, and knowledge of nurses, is an important topic that continues to grow in research. Although technologies such as electronic medical records are also relevant, the focus of research seems to be more on behavioral factors that influence documentation quality. This study provides guidance for researchers to identify gaps in the literature that could be further explored, especially in the development of more effective and integrated documentation systems. Keywords: Compliance, Completeness, Nursing Care Documentation, Motivation, Knowledge